Transportation Systems, Problems and Challenges Affect Their Contribution to an Analysis of the Issues of the Economic Development in Nigeria - Abalaka James Nda; Ajiteru S.A.R; Sulaiman T.H (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this article is to examine the current issues and difficulties that Nigeria's four main transportation modes are facing. The data utilized in this research were gathered by field observations, oral interviews, and a thorough literature search of books, journals, and pertinent government documents. After discussing the difficulties and issues affecting each mode's ability to continue contributing to the nation's economic development, the historical evolution of each mode and its historical role in that development are provided. The main effects of driving being preferred over other modes of transportation are the environmental issues associated with driving and the high rate of traffic accidents on Nigerian roads. There are numerous inland waterways of capacity that is underutilized as a result of the antiquated railway system. Despite being widely utilized, the airways still require significant development and refinement. In order for these modes to continue contributing to Nigeria's economic development, the study offered viable solutions to these issues and obstacles.